Adolescent pregnancy in Sao Tome and Principe: are there different obstetric and perinatal outcomes? - Alexandra Vasconcelos; Nelson Bandeira; Swasilanne Sousa; Maria Céu Machado; Filomena Pereira (BMC, 2022)
Abstract Background Adolescent childbirth is a major public health problem in Sao Tome and Principe (STP). Adolescent pregnancy and childbirth can carry a risk of morbidity associated with the physiological and sociological characteristics of teenage girls. This study aims to identify the main adverse obstetric and perinatal outcomes for adolescent pregnancies in the Hospital Dr. Ayres de Menezes (HAM), the only hospital in STP. Methods An institution-based cross-sectional study. Pregnant women ≤ 19 years of age (n = 104) were compared to non-adolescent women (n = 414). The obstetric and perinatal outcomes were compared between groups using the t test. Odds ratio (OR) were calculated through Cochran's and Mantel-Haenszel statistics test for odds ratio equal to 1, 95% confidence intervals (CI) and p values (p < 0.05) were considered significant. Results The adverse perinatal outcomes imputable to adolescent births were foetal distress with low first minute Apgar score < 7 (OR 1.94, 95% CI 1.18-3.18, p = 0.009) and performance of neonatal resuscitation manoeuvres (OR 2.4, 95% CI 1.07-5.38, p = 0.032). Compared to older mothers, teenage girls were likely to have a non-statistically significant threefold higher risk of having an obstructed labour (OR 3.40, 95% CI 0.89-12.94, p = 0.07). Other perinatal outcomes as neonatal asphyxia, risk for cerebral palsy, premature birth, early neonatal infection, and neonatal death were identical between groups as well as maternal anaemia, mode of delivery or other obstetrical outcomes. Conclusion Adolescent pregnancies were associated with worse perinatal outcomes as foetal distress and higher need for neonatal resuscitation manoeuvres. This study may support STP health authorities in their efforts to make Sustainable Development Goals 3 (good health and wellbeing), 4 (quality education) and 5 (gender equality) a reality by 2030, since it identifies specific problems that need to be addressed to improve maternal adolescent health.